Profiling translatomes of discrete cell populations resolves altered cellular priorities during hypoxia in Arabidopsis - Mustroph, Angelika (2009)
Multicellular organs are composed of distinct cell types with unique assemblages of translated mRNAs. Here, ribosome-associated mRNAs were immunopurified from specific cell populations of intact seedlings using Arabidopsis thaliana lines expressing a FLAG-epitope tagged ribosomal protein L18 (FLAG-RPL18) via developmentally regulated promoters. The profiling of mRNAs in ribosome complexes, referred to as the translatome, identified differentially expressed mRNAs in 21 cell populations defined by cell-specific expression of FLAG-RPL18. Phloem companion cells of the root and shoot had the most distinctive translatomes. When seedlings were exposed to a brief period of hypoxia, a pronounced reprioritization of mRNA enrichment in the cell-specific translatomes occurred, including a ubiquitous rise in 49 mRNAs encoding transcription factors, signaling proteins, anaerobic metabolism enzymes, and uncharacterized proteins. Translatome profiling also exposed an intricate molecular signature of transcription factor (TF) family member mRNAs that was markedly reconfigured by hypoxia at global and cell-specific levels. In addition to the demonstration of the complexity and plasticity of cell-specific populations of ribosome-associated mRNAs, this study provides an in silico dataset for recognition of differentially expressed genes at the cell-, region-, and organ-specific levels.